Analisis Kemampuan Pemecahan Masalah Matematis Peserta Didik di Sekolah Dasar - Patih, Tandri; Herman, Herman; Haryati, Haryati; Hadi, Amanda La; Riansyah, Firman; Halistin, Halistin (IAIN Kendari, 2024)
The aim of this study is to describe the mathematical problem-solving abilities of students at a public school in Konawe District. This research employs a qualitative method. The study involves 12 student participants selected through purposive sampling technique. Data collection includes tests, interviews, and documentation. Data analysis involves data reduction, data presentation, and drawing conclusions. The research results indicate that 8.3% of students have high and moderate problem-solving abilities, while 83.4% have low problem-solving abilities. In terms of understanding the problem, students with high and moderate abilities demonstrate adequate understanding, although they struggle with determining the final answer accurately. On the other hand, students with low problem-solving abilities only write down what they know. Errors in solving mathematical problem-solving abilities are mainly found in the process of devising a mathematical problem-solving plan. Additionally, during the reviewing stage, students do not conduct thorough and accurate reviews. The level of mathematical problem-solving abilities is influenced by the lack of practice in solving story problems related to fractions and integers.Keywords: Integers, mathematics, problem solving ability